c-823=-23c-7

Simple and best practice solution for c-823=-23c-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for c-823=-23c-7 equation:


Simplifying
c + -823 = -23c + -7

Reorder the terms:
-823 + c = -23c + -7

Reorder the terms:
-823 + c = -7 + -23c

Solving
-823 + c = -7 + -23c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '23c' to each side of the equation.
-823 + c + 23c = -7 + -23c + 23c

Combine like terms: c + 23c = 24c
-823 + 24c = -7 + -23c + 23c

Combine like terms: -23c + 23c = 0
-823 + 24c = -7 + 0
-823 + 24c = -7

Add '823' to each side of the equation.
-823 + 823 + 24c = -7 + 823

Combine like terms: -823 + 823 = 0
0 + 24c = -7 + 823
24c = -7 + 823

Combine like terms: -7 + 823 = 816
24c = 816

Divide each side by '24'.
c = 34

Simplifying
c = 34

See similar equations:

| 6q=24q+7 | | 8x+1+5x-2=90 | | -3x+69=x+189 | | 8(3a+6)=9(2a-2) | | 8.95m+.06=0m+.10 | | 6(y-9)=4(y-5) | | 2xsquared+5x+4=0 | | 7q+14=5(2q)-55 | | (16b-2)-5(3b+3)=-4 | | sqrt(8-x)+4-sqrt(4x-3)=0 | | (3x+2)(2x-1)=0 | | 10x-15=25-2x | | 5x+7=6+3x+1+2x | | ln(8-9x)=-1 | | ln(9x+8)=-1 | | -6q+72=q+269 | | 2(3+w)=41 | | 30x+5=125 | | 13p+3=p-597 | | x+(x+2)=108 | | 5(2x-4)=3(3x+6) | | (3(x-5a+9))= | | 5/3*2= | | x+12=4x-6 | | 20+1.25d=2.5d | | 5x-15x-7=5(4x+4) | | 8-n=1+2n-2n | | v+162=-4v-3 | | .04x+x=5200000 | | 117x^2+8xy+117y^2-484x-484y=12705 | | 6+x=26 | | b+84=-5b-6 |

Equations solver categories